The association of rs11190870 near LBX1 with the susceptibility and severity of AIS, a meta-analysis. (June 2018) - Li, Yu-Lin; Gao, Shi-Jie; Xu, Hong; Liu, Yang; Li, Hai-Liang; Chen, Xing-Yu; Ning, Guang-Zhi; Feng, Shi-Qing
Abstract: Background: Adolescent idiopathic scoliosis (AIS) is the most common structural deformity of the spine. Genetics constitute largely to AIS, and the rs11190870 polymorphism has the potential for use in public health and clinical settings as a predictor of AIS risk. The aim of the present meta-analysis was to provide exhaustive evidence to evaluate the association of rs11190870 with the susceptibility and severity of adolescent idiopathic scoliosis (AIS) in multiple ethnic groups and different genders. Materials and Methods: The professional databases, including PubMed, Embase, Social Sciences Citation Index, CINAHL, and International Bibliography of the Social Sciences, were searched from 1966 to October 2015. No language restriction was applied. Reference lists of all the selected articles were hand-searched for any additional studies. Three authors independently extracted data from all eligible studies. The data were analyzed by meta-analysis using fixed-effects or random-effects models with mean differences and risk ratios for continuous and dichotomous variables, respectively. Results: Eight studies were included, and the pooled analysis suggested that the T genotype of SNP rs11190870 leads to a higher risk of AIS in multiple ethnic groups regardless of gender (Total:OR, 1.66, 95% CI 1.53, 1.79; I 2  = 37.3%, P = 0.000, Female: OR, 1.62, 95% CI 1.50, 1.73; I 2  = 26.7%, P = 0.000, Male: OR, 1.79, 95% CI 1.38, 2.20; I2 = 0.00%, P = 0.000). Additionally, the TT and TC genotype had a larger Cobb angle than those with the CC genotype in the overall and female Asian populations. Conclusion: A significant association of rs11190870 with AIS was observed in multiple ethnic groups regardless of gender. Additionally, a significant association was found between rs11190870 and curve severity in the overall and female Asian populations. Due to the limited data and clinical heterogeneity, further studies with large sample sizes are required. Highlights: A significant association of rs11190870 with AIS was observed in multiple ethnic groups regardless of gender. The TT and TC genotype had a larger Cobb angle than those with the CC genotype in the overall and female Asian populations. Further studies on the association of rs11190870 with AIS susceptibility and severity in multiple ethnic groups are necessary.